OPTIMIZATION OF BUTTERFLY PEA EXTRACT PEEL-OFF MASK WITH VARIATIONS OF POLYVINYL ALCOHOL AND IOTA CARRAGEENAN USING FACTORIAL DESIGN - Dina Permata, Wijaya; Shaum, Shiyan; Nabilah Putri, Hadiani; Herlina, Herlina; Mutia Sari, Wardana (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2025)
ABSTRACT The butterfly pea flower (Clitoria ternatea) contains antioxidants that help combat premature skin aging. Peel-off masks are popular with consumers as topical formulations because they are unique and practical. An essential component of peel-off masks is the gelling agent Polyvinyl Alcohol (PVA), which acts as a film-forming agent. However, PVA at the wrong concentration can result poor mask physical properties. Combining PVA with other gelling agents can obtain peel-off masks with better physical properties. This study aims to identify the effect of PVA and iota carrageenan on the optimal formula of peel-off masks regarding physical properties, stability, and antioxidant activity. Butterfly pea flower extract was obtained by maceration in 70% ethanol. Optimization of PVA and iota carrageenan was conducted using a factorial design method, observing responses such as viscosity, spreadability, and drying time. Peel-off masks with butterfly pea flower extract were prepared with concentration variations of PVA (6%, 10%) and iota carrageenan (0.5%, 1%). The optimal formula was then tested for stability using cycling test method and for antioxidant activity using DPPH method. Increasing concentrations of PVA and iota carrageenan significantly affects viscosity, spreadability, and drying time, with a p-value < 0.05. The optimal peel-off mask formula contained 16% PVA and 0.5% iota carrageenan, with a viscosity of 16.473 cPs, spreadability of 5.6 cm, and drying time of 23 minutes and 11 seconds. The optimal formula demonstrated good stability during storage, with a significance p-value > 0.05, and was categorized as having weak antioxidant activity with an IC50 value 171.738 µg/mL.